DETERMINAN KEPATUHAN PAJAK UMKM DI ERA DIGITAL: A SYSTEMATIC LITERATURE REVIEW - Yustika Jauhari; Nurul Maghfirah Surianto (CV. Denasya Smart Publisher, 2026)
Digital tax transformation through the implementation of services such as e-filing, e-billing, and Coretax has changed the tax compliance patterns of MSMEs taxpayers in Indonesia. Tax digitalization not only provides administrative convenience but also requires technological readiness and digital literacy among MSMEs actors. However, previous studies on MSME tax compliance in the digital era still show relatively inconsistent findings and tend to discuss certain factors partially. This study aims to analyze the determinants of MSME tax compliance in the digital era using a Systematic Literature Review (SLR) approach. The study was conducted through the stages of planning, conducting, and reporting. The article search process was carried out using Google Scholar within the publication period of 2020–2026 using keywords related to MSME tax compliance and tax digitalization. The selected articles were screened using inclusion criteria, exclusion criteria, and quality assessment. The results indicate that the determinants of MSME tax compliance in the digital era are influenced by digital literacy, tax knowledge, e-tax adoption, technology utilization, and Coretax implementation. Tax digitalization has proven to improve tax compliance through service convenience, administrative efficiency, and improved tax service quality. However, low digital literacy and limited technological readiness remain obstacles in implementing digital taxation systems for MSMEs. This study contributes to mapping the determinants of digital-based MSME tax compliance as a basis for developing more effective digital taxation policies.